PENGARUH CAR, BOPO, NPL, DAN LDR TERHADAP NET INTEREST MARGIN BANK DI INDONESIA (Studi Kasus Periode 2006-2009) - , Bagus Prabowo, Prof. Dr. Eduardus Tandelilin, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In period 2008-2009, the banking industry in Indonesia has increased in performance which is indicated by the increase in the ratio of Net Interest Margin (NIM), but this is not too good for the real sector because it creates burden for entrepreneurs because of the high loan interest rates. The research was conducted to analyze factors that influence NIM such as variables of Capital Adequacy Ratio (CAR), Operating Expenses and Operating Income (BOPO), Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR). There have been many previous studies but there have been different results, the results obtained from these studies are inconsistent. This inconsistent result happened despite using the same research variables, so another research is needed to re-analyze the variables of the study. The sample used in this study were all banking companies listed in Indonesia Stock Exchange from 2006-2009. The method used in sample selection was purposive sampling, conducted until 19 banking companies were obtained. Analysis technique used is multiple linear regression and hypothesis testing using t-statistics. During the observation it is shown that the study data is normally distributed by using the Kolmogorov-Smirnov test. The results showed that the variable CAR has negative but not significant effect on NIM. BOPO variable has significantly negative effect on NIM. NPL variable has negative but not significant effect on NIM. LDR variable has positive and significant effect on NIM.